2009
DOI: 10.1148/radiol.2521081534
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Glioblastoma Multiforme: ADC Histogram Analysis Predicts Response to Bevacizumab Treatment

Abstract: Pretreatment ADC histogram analysis can stratify progression-free survival in bevacizumab-treated patients with recurrent GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
241
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(255 citation statements)
references
References 31 publications
7
241
3
4
Order By: Relevance
“…However, most of the IDH1 mutants had large areas of nonenhancing tumor, potentially diminishing this limitation. Although the ability to identify nonenhancing tumor with high interobserver reliability has previously been demonstrated, 46 the single-reader methodology used also is a limitation of this study. Approximately half of our patients received subtotal resection, and 12 had biopsy only.…”
Section: Discussionmentioning
confidence: 94%
“…However, most of the IDH1 mutants had large areas of nonenhancing tumor, potentially diminishing this limitation. Although the ability to identify nonenhancing tumor with high interobserver reliability has previously been demonstrated, 46 the single-reader methodology used also is a limitation of this study. Approximately half of our patients received subtotal resection, and 12 had biopsy only.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, DWI values of gliomas before treatment correlated with the probability of response to therapy with bevacizumab in a study performed by Pope et al (118). Functional diffusion maps show promise as a way of providing an early surrogate marker for FIGURE 8.…”
Section: Mrimentioning
confidence: 96%
“…In children, the percentage change of choline or NAA combined with perfusion measurements in serial MRI examinations was found to be useful in predicting tumor progression (117). Before antiangiogenic therapy, ADC analysis of gliomas tended to predict progression-free survival in recurrent glioblastoma multiforme patients (118).…”
Section: Mrimentioning
confidence: 99%
“…Therefore, it may better reflect how many pixels undergo change in ADC after treatment [8,115] . It has been demonstrated that ADC histogram analysis may be a superior and quicker biomarker of tumor response to bevacizumab than tumor volume [116] . With the spatially varying change in ADC after treatment, an ideal approach is to analyze the pixels present both before and after treatment with spatial tags to detect any change in ADC pixel by pixel.…”
Section: Adc-quantification Of Dwimentioning
confidence: 99%